Deciphering the mechanism and function of Hsp100 unfoldases from protein structure. (16th December 2022) - Lee, Grace; Kim, Rebecca S.; Lee, Sang Bum; Lee, Sukyeong; Tsai, Francis T.F.
Abstract : Hsp100 chaperones, also known as Clp proteins, constitute a family of ring-forming ATPases that differ in 3D structure and cellular function from other stress-inducible molecular chaperones. While the vast majority of ATP-dependent molecular chaperones promote the folding of either the nascent chain or a newly imported polypeptide to reach its native conformation, Hsp100 chaperones harness metabolic energy to perform the reverse and facilitate the unfolding of a misfolded polypeptide or protein aggregate. It is now known that inside cells and organelles, different Hsp100 members are involved in rescuing stress-damaged proteins from a previously aggregated state or in recycling polypeptides marked for degradation. Protein degradation is mediated by a barrel-shaped peptidase that physically associates with the Hsp100 hexamer to form a two-component system. Notable examples include the ClpA:ClpP (ClpAP) and ClpX:ClpP (ClpXP) proteases that resemble the ring-forming FtsH and Lon proteases, which unlike ClpAP and ClpXP, feature the ATP-binding and proteolytic domains in a single polypeptide chain. Recent advances in electron cryomicroscopy (cryoEM) together with single-molecule biophysical studies have now provided new mechanistic insight into the structure and function of this remarkable group of macromolecular machines.